1993
DOI: 10.3109/10550499309113940
|View full text |Cite
|
Sign up to set email alerts
|

Urine Screening for Marijuana Among Methadone-Maintained Patients

Abstract: Ninety‐eight male patients on methadone maintenance treatment provided weekly urine screens for typical substances of abuse and periodic screens for 9‐carboxy‐tetrahydrocannabinol (THC). Although different in some demographics and personality characteristics, patients who were THC‐positive (THC+; n = 54, 55.1%) were no more likely to use other illicit drugs and showed similar treatment retention, employment, and cognitive function to those who were THC‐negative. THC+ patients reported more marijuana use at adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
29
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 0 publications
7
29
1
Order By: Relevance
“…On the other hand, continuing to use an addictive drug, such as marijuana, could interfere with efforts to achieve abstinence from other drugs. Or it may have no effect (Budney et al, 1998; Hill et al, 2013; Church et al, 2001; Epstein and Preston, 2003; Nirenberg et al, 1996; Saxon et al, 1993; Alessi et al, 2011; Budney et al, 1996; Darke et al, 2006). Prior studies lend some support for each of these possibilities and hence findings among previously published studies are inconsistent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, continuing to use an addictive drug, such as marijuana, could interfere with efforts to achieve abstinence from other drugs. Or it may have no effect (Budney et al, 1998; Hill et al, 2013; Church et al, 2001; Epstein and Preston, 2003; Nirenberg et al, 1996; Saxon et al, 1993; Alessi et al, 2011; Budney et al, 1996; Darke et al, 2006). Prior studies lend some support for each of these possibilities and hence findings among previously published studies are inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…But findings about marijuana’s effects on use of other substances and the need to address it during addiction treatment for other substances are not uniform (Hill et al, 2013; Wasserman et al, 1998; Church et al, 2001; Epstein and Preston, 2003; Nirenberg et al, 1996; Saxon et al, 1993; Aharonovich et al, 2005; Alessi et al, 2011; Budney et al, 1996; Kadden et al, 2009). Many find no association between marijuana use and outcome of addiction treatment for other substances (Budney et al, 1996; Church et al, 2001; Epstein and Preston, 2003; Hill et al, 2013; Nirenberg et al, 1996; Saxon et al, 1993) and one small study suggested that marijuana use helped crack cocaine addiction (Labigalini et al, 1999). Another small study, however, suggests that addressing marijuana use may lead to more use of alcohol (Peters and Hughes, 2010) and at least two prospective studies suggest that marijuana use is associated with worse addiction treatment outcomes (Aharonovich et al, 2005; Wasserman et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…There were no significant correlations between cannabis use and the likelihood of testing positive for opioid, benzodiazepine or cocaine use in a group of buprenorphine-treated persons (Budney et al, 1998), or in methadone-maintained individuals (Saxon, 1993, Epstein and Preston, 2003, Scavone et al, 2013). Findings from a meta-analysis on predictors of substance use in treatment-seeking opioid dependent individuals found evidence for concurrent cannabis and opioid use during treatment, but no prospective effects of cannabis on increased opioid use following completion of treatment (Brewer et al, 1998).…”
Section: Potential Therapeutic Targets Of Cannabinoid-opioid Intermentioning
confidence: 94%
“…For example, Marammani observed within a cohort of 1090 heroin-dependent individuals presenting for methadone maintenance between 1994 and 2005, that 64.6% of men and 57.1% of females reported concurrent opioid and cannabis use when entering treatment (Maremmani et al, 2010). One study of 98 males on MMT found that 55.1% used cannabis during treatment (Saxon, 1993), while another study reported an even higher 79% rate of use (Nirenberg, 1996). Cannabis use was evaluated prior to and during treatment in a sample of 196 persons in an Israeli methadone maintenance program.…”
Section: Potential Therapeutic Targets Of Cannabinoid-opioid Intermentioning
confidence: 99%
See 1 more Smart Citation